Identifying Andean crop processing and consumption in the area of Quebrada de Humahuaca (Argentina) under Inca domination - Musaubach, María Gabriela (2020)
Cooking practices were an integral part of the political, social and productive life of pre-Hispanic communities. During the Inca domination, new cooking and commensality practices were put into practice for the first time, which brought together new forms of status and social recognition. This paper focuses on Andean crop processing techniques and consumption during the Inca period. Through inter-disciplinary analyses of plant-foods and ceramic vessels we investigate culinary practices associated to domestic and non-domestic elite contexts and evaluate the role of different foods for the Inca communities of the area of Quebrada de Humahuaca (North of Argentina). The analysed materials were recovered at two major archaeological sites in the southern part of Quebrada de Humahuaca, called Pucara de Volcán and Esquina de Huajra. They are conglomerated settlements with an Inca occupation dated to circa 430 BP. In order to study culinary techniques we followed and developed two main approaches: archaeobotanical studies of plant micro-remains and use-wear analysis of pottery. The first study was carried out on grinding stone tools recovered in Pucara de Volcán and dental calculus of two individuals buried in Esquina de Huajra. Use-wear analysis were carried out in ceramic vessels from both sites, and abrasive and non-abrasive processes were considered to infer functional aspects linked to plant processing activities. These analyses are complemented with the contextual study of the materials, to highlight differences between domestic and non-domestic contexts. The results of this study highlight that Zea mays (maize), Phaseolus sp. (beans) and tubers were important ingredients of ancient recipes. The presence of diverse grinding stone tools indicates the preparation of flour. Finally, vessels with traces of soot and abrasive processes point out to the processing of stew-like foodstuffs.